Analisis Deteksi Dini Penentu Kompensasi - Oberlian; Karyadi, Sugeng; Suparman; Ismuhadi; Mustika (Jurnal EMT KITA, 2025)
This study aims to empirically test the influence of work experience and work performance on employee compensation at PT. GCF Semarang. This research uses quantitative methods. The researcher uses primary data, namely information obtained directly from respondents as seen from the answers to the questionnaires that have been distributed. The researcher applies a modified Likert scale with a score of 1-5. Sampling uses the census method so that the number of samples is the same as the population of 69 employees of PT. GCF Semarang. Data analysis uses the Partial Least Square (PLS) approach assisted by SmartPLS software version 3.29. The results of this study indicate that partially work experience and work performance positively and significantly affect employee compensation at PT. GCF Semarang. On the other hand, simultaneously work experience and work performance positively and significantly affect employee compensation at PT. GCF Semarang.